419 Intramuscular immunization with rVCG-MECA vaccine elicits stronger chlamydial specific immune response than intranasal immunization - Medhavi FNU; Tanner Tayhlor; Richardson Shakyra; Jones Leandra; Bell Counrtnee; Josesph U. Igietseme; Omosun Yusuf; Eko Francis (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: We prioritize Chlamydia’s public health impact, aim to develop rVCG-MECA for practical use, study robust immunity for effective strategies, and assess animal models for human vaccination adaptation. Our work highlights rVCG-MECA’s translational significance in public health. METHODS/STUDY POPULATION: Female Mice C57BL/6J mice (N=8) were immunized intramuscularly(IM) and intranasally(IN) and boosted twice, two weeks apart, with rVCG-MECA, once with live Chlamydia (C. trachomatis serovar D elementary bodies) and PBS. Specific mucosal and systemic immune responses were characterized. Vaccine efficacy was determined from chlamydia shedding following the transcervical challenge. Additionally, Chlamydia-specific cytokine (IFN-γ and IL-4) production by splenic and ILN T cells was assessed after 16 weeks RESULTS/ANTICIPATED RESULTS: Immunization with rVCG-MECA via intramuscular and intranasal routes triggered notable humoral responses in systemic and mucosal tissues. Intramuscular vaccination produced higher IgG2c levels in both tissues, while intranasal vaccination led to elevated IgA levels in mucosal tissues. rVCG-MECA-immunized mice exhibited significantly higher IFN-γ (Th1) secretion compared to IL-4 (Th2), with intramuscular immunization showing the highest IFN-γ levels. These findings anticipate robust immune responses, promising protection against Chlamydia, particularly through the intra muscular route. Overall, our results support rVCG-MECA as a promising Chlamydia vaccine, aligned with public health goals. DISCUSSION/SIGNIFICANCE: This study suggests that IM and IN immunization with rVCG-MECA induces immune effectors such as IFN-gamma and IgG2c that mediate chlamydial clearance in the genetical tract.